World agenda of livestock research in developing countries with special reference to Asia - Fitzhugh, H.A. (Japanese Society of Zootechnical Science, 1996)
Demand for livestock products in Asia is expected to grow at a faster rate over the next two decades than in any other region. The factors driving demand in Asia include population increase, expanded urbanisation and improved income. Devendra (1996) predicts that industrial scale poultry and swine operations will provide an increasing share of meat consumed especially in East Asia. However, ruminants will continue to play a major role in smallholder, low input crop-livestock systems, including the use of cattle and buffalo for traction. This paper presents and discusses world agenda of livestock research in developing countries with special reference to Asia. Topics of discussion include research based livestock Development, programme objectives of ILRI, aims of System Wide Livestock Programme (SLP), livestock research priorities, and livestock improvement work plan in upland farming systems.